Dampak Kecerdasan Buatan (AI) pada Pengambilan Keputusan HR: Studi Kualitatif tentang Bias Algorithmik dalam Seleksi Karyawan - Dipoatmodjo, Tenri Sayu Puspitaningsih (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the impact of artificial intelligence (AI) implementation in human resource decision-making, particularly in the employee selection stage in Makassar City. Using a qualitative approach and case study method, this research explores the perceptions of HR practitioners and candidates regarding potential algorithmic bias in CV screening and virtual interviews. The findings reveal that while AI improves efficiency, it may also pose risks of hidden discrimination due to historical data bias and rigid system parameters. This study highlights the importance of balancing technological tools with human judgment to ensure a fair, inclusive, and ethical selection process. The results contribute theoretically to the discourse on algorithmic fairness and offer practical implications for organizations adopting AI in HR management.